2013
DOI: 10.5194/nhess-13-1085-2013
|View full text |Cite
|
Sign up to set email alerts
|

Using a cloud electrification model to study relationships between lightning activity and cloud microphysical structure

Abstract: In this study a one-dimensional numerical cloud electrification model, called the Explicit Microphysics Thunderstorm Model (EMTM), is used to find quantitative relationships between the simulated electrical activity and microphysical properties in convective clouds. The model, based on an explicit microphysics scheme coupled to an ice–ice noninductive electrification scheme, allows us to interpret the connection of cloud microphysical structure with charge density distribution within the cloud, and to study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 73 publications
1
12
0
1
Order By: Relevance
“…However, it is worth noting that the LINET network detects more CG than IC strokes, and the lower correlation could also be due to the large baseline between sensors near the coast (Zinner et al, 2013), which can cause a reduced detection efficiency and significant impact on the detection of weak ICs. In particular Formenton et al (2013) showed higher LINET performances in ICs' detection in the area of Munich compared to the area of Rome where baseline is larger. Since the best correlation was found for the −CG, the time evolution of the graupel total mass and −CG was examined (Fig.…”
Section: Dual-polarization Radar Analysis and Lightning Activitymentioning
confidence: 88%
“…However, it is worth noting that the LINET network detects more CG than IC strokes, and the lower correlation could also be due to the large baseline between sensors near the coast (Zinner et al, 2013), which can cause a reduced detection efficiency and significant impact on the detection of weak ICs. In particular Formenton et al (2013) showed higher LINET performances in ICs' detection in the area of Munich compared to the area of Rome where baseline is larger. Since the best correlation was found for the −CG, the time evolution of the graupel total mass and −CG was examined (Fig.…”
Section: Dual-polarization Radar Analysis and Lightning Activitymentioning
confidence: 88%
“…These parameters diagnosed from a given snow mass mixing ratio at every grid Reviews of Geophysics 10.1002/2014RG000468 point for each time step. Formenton et al [2013aFormenton et al [ , 2013b used an observed relation between the parameters of the gamma distributions, obtained by Heymsfield et al [2002] in an analysis of aircraft data from various field campaigns.…”
Section: Approaches Used In Bulk Schemes To Improve the Approximationmentioning
confidence: 99%
“…This generates the in-cloud electric field distribution that initiates lightning when the field exceeds values of 100-250 kV m −1 (Marshall et al, 1995a, b). This is the foundation for numerical models like the 1-D Explicit Microphysics Thunderstorm Model (Solomon and Baker, 1996;Solomon et al, 2005) used to study the relationships between lightning activity and cloud microphysical structure (Formenton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%